Mindfulness-based stress reduction for elementary school teachers: a randomized controlled trial - Lensen, Johanna H.; Stoltz, Sabine E. M. J.; Kleinjan, Marloes; Kraiss, Jannis T.; Scholte, Ron H. J.; Speckens, Anne E. M. (Frontiers in Education, 2024)
Educators frequently grapple with elevated levels of job-related stress, heightening the risk of mental health issues. Although Mindfulness-Based Stress Reduction (MBSR) has demonstrated effectiveness in reducing stress among the general populace, its implementation among educators, especially in non-U.S. settings, has received limited exploration.While Mindfulness-Based Stress Reduction (MBSR) has proven efficacious in alleviating stress among the general population, its application to educators, particularly in non-U.S. contexts, remains underexplored . This preregistered randomized-controlled trial investigates the effectiveness of the standard MBSR in reducing perceived stress among Dutch elementary school teachers. Additionally, it examines the impact of MBSR on mindfulness skills, emotion regulation, and self-compassion as secondary proximal outcomes, along with exploring its influence on teacher self-efficacy, perceived pupilteacher relationships, and classroom climate quality as secondary distal outcomes. Involving 146 teachers randomly assigned to either the intervention (n = 72) or waitlist-control condition (n = 74), assessments were conducted pre-and post-intervention or control period, with a three-month followup. Participants in the intervention reported significantly lower perceived stress compared to the control group, demonstrating a substantial effect size at post-treatment (d = -0.84) and a moderate effect at follow-up (d = -0.69). MBSR not only yielded improvements in personal well-being but also positively impacted teacher self-efficacy and classroom climate quality at both post-treatment and follow-up. These positive outcomes aligned with enhancements in mindfulness skills, emotion regulation, and self-compassion. However, no significant effects were observed on the pupil-teacher relationship. Exploratory analyses revealed no moderation effects based on past or present psychological problems, school weight/pupil population, years of experience, or age on perceived stress at post-measurement. Furthermore, the study examined the potential influence of COVID-19 on the results, concluding that the pandemic had no discernible impact. These findings advocate for the widespread adoption of the standard MBSR program as a means of enhancing the well-being of elementary school teachers.